Recharacterization of Rhynchoheterotricha Freeman (Diptera, Sciaroidea), with description of R. chandleri sp. n. from South Africa - Hippa, Heikki; Vilkamaa, Pekka (Zootaxa, 2006)
Rhynchoheterotricha chandleri sp. n. is described from South Africa. It differs from the earlier known R. stuckenbergae Freeman by having a setose wing membrane and a proboscis that is only about half the height of the head rather than about three times as long as the head. Through a detailed morphological analysis, the genus is recharacterized. The previously unknown female morphology is presented.